Asymmetrical atrophy of thalamic subnuclei in Alzheimer's disease and amyloid‐positive mild cognitive impairment is associated with key clinical features. Issue 1 (1st December 2019) - Low, Audrey; Mak, Elijah; Malpetti, Maura; Chouliaras, Leonidas; Nicastro, Nicolas; Su, Li; Holland, Negin; Rittman, Timothy; Rodríguez, Patricia Vázquez; Passamonti, Luca; Bevan‐Jones, W Richard; Jones, PP Simon; et al.
Abstract: Introduction: Although widespread cortical asymmetries have been identified in Alzheimer's disease (AD), thalamic asymmetries and their relevance to clinical severity in AD remain unclear. Methods: Lateralization indices were computed for individual thalamic subnuclei of 65 participants (33 healthy controls, 14 amyloid‐positive patients with mild cognitive impairment, and 18 patients with AD dementia). We compared lateralization indices across diagnostic groups and correlated them with clinical measures. Results: Although overall asymmetry of the thalamus did not differ between groups, greater leftward lateralization of atrophy in the ventral nuclei was demonstrated in AD, compared with controls and amyloid‐positive mild cognitive impairment. Increased posterior ventrolateral and ventromedial nuclei asymmetry were associated with worse cognitive dysfunction, informant‐reported neuropsychiatric symptoms, and functional ability. Discussion: Leftward ventral thalamic atrophy was associated with disease severity in AD. Our findings suggest the clinically relevant involvement of thalamic nuclei in the pathophysiology of AD.